Characterization and Effect of Using Peanut Seed Oil Methyl Ester as a Fuel in a Low Heat Rejection Diesel Engine - Hazar, Hanbey; Ozturk, Ugur; Gul, Hakan (Amer Chemical Soc, 2016)
To decrease hazardous emissions of internal combustion engines and to improve the combustion and thermal efficiency, thermal barrier coatings were applied. In this experimental study, cylinder, piston, exhaust, and inlet valves, which are combustion chamber components, were coated with a ceramic material and this enabled the engine to gain a low heat rejection feature. Cylinder, exhaust, and inlet valves of the diesel engine used in the tests were coated with ekabor-2 commercial powder, which is a ceramic material, to a thickness of 50,um using the boronizing method. The piston of a diesel engine was coated in 300 inn thickness with bor-based powder using the plasma-coating method. Peanut seed oil methyl ester (PSME) was produced using the transesterification method. In addition, diethyl ether additive materials were used to improve the properties of diesel fuel, PSME, and its mixture. Diethyl ether was blended with test fuels, which were used as a pilot'fuel, at the volumetric ratios of 4 and 8%. As a result of the thermal barrier coating, the brake-specific fuel consumption, carbon monoxide, hydrocarbon, and smoke density values of the diesel engine decreased, whereas nitrogen oxides, carbon dioxide, thermal efficiency, and exhaust gas temperature increased.
Keywords: Compression-Ignition Engine; Diethyl-Ether; Emission Characteristics; Performance; Combustion; Biodiesel; Blends; Injection